2022
DOI: 10.1186/s12903-022-02365-1
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of associations between condylar morphology, ramus height, and mandibular plane angle in various vertical skeletal patterns: a digital radiographic study

Abstract: Background To evaluate condylar morphology, ramus height, and asymmetry indexes in patients with different vertical skeletal patterns and to determine the association between condylar and ramal measurements with the mandibular plane angle. Methods Dental panoramic radiographs of 60 patients with different skeletal patterns were evaluated. According to the cranial base (Sella-Nasion)-mandibular plane (SN-MP) angle, the patients were divided into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
1
0
0
1
Order By: Relevance
“…Other studies, however, have reported no significant difference between the right and left sides of the same individual. [ 16 33 ] In regards to Cvol, the current study reported significant differences in Cvol between the right and left sides, a finding that concurs with the results of a study by Shetty et al . [ 34 ] On the other hand, other studies have reported different findings.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies, however, have reported no significant difference between the right and left sides of the same individual. [ 16 33 ] In regards to Cvol, the current study reported significant differences in Cvol between the right and left sides, a finding that concurs with the results of a study by Shetty et al . [ 34 ] On the other hand, other studies have reported different findings.…”
Section: Discussionsupporting
confidence: 92%
“…15 Namun, radiografi panoramik memiliki keuntungan seperti dapat digunakan secara rutin dalam pemeriksaan gigi, biaya rendah, dan memaparkan dosis radiasi yang relatif rendah pada pasien dibandingkan cone-beam computed tomography (CBCT) yang dianggap sebagai standar untuk pemeriksaan kraniofasial. 25 Terdapat limitasi lainnya pada penelitian ini, yaitu perbandingan jumlah sampel yang relatif tidak setara dan saat menentukan gejala TMD hanya menggunakan kuesioner indeks TMD-DI tanpa dilakukan pemeriksaan klinis. Perlu dilakukan penelitian lebih lanjut untuk mengetahui hubungan asimetri kondilus yang terjadi pada pasien bergigi lengkap dengan berbagai faktor penyebabnya.…”
Section: Pembahasanunclassified